The honey of Plebeia molesta and other melliferous insects in the peasant culture of the Northwest of Córdoba, Argentina - Geisa, Melisa Gabriela; Hilgert, Norma Inés (Ethnobiology and Conservation, 2019)
Bees called meliponas (family Apidae, tribe Meliponini) are native stingless bees (ANSA) whose products (honey and other elements from the hive) have been employed by various indigenous and peasant cultures since ancient times. This study lists the native honeybee species known to criollos from northwest Córdoba. It also analyzes in particular the relationship between peasants living in three different environments in the region and the uses they assign to Plebeia molesta honey. Semistructured interviews were conducted with 42 key interlocutors. To analyze the obtained information qualitative and quantitative methods were used. Local people recognize 4 native melliferous insects, being the one called “quella” the most important. Its honey is used mainly for medicinal purposes and as food. The predominant use as medicine is ingestion in pure form (45%) and the most frequently treated conditions are those related to the respiratory system (88.53%). In relation to the changes perceived in the availability of this resource, 75% of the interlocutors considered that the frequency of nest encounters has decreased in the last decades. The assigned uses of honey show a high variability in relation to the sociocultural and occupational characteristics of the inhabitants. It is concluded that this honey is a valuable resource for farmers in the region. Given the perceived decrease of these populations, management and conservation strategies should be implemented that,incorporating the peasant point of view, guarantee their accessibility and perpetuity.